Visibility and Apparent Size of Néel-Type Magnetic Skyrmions in Fresnel Defocus Images of Multilayer Films. (December 2021) - Denneulin, Thibaud; Caron, Jan; Müller-Caspary, Knut; Boulle, Olivier; Kovács, András; Dunin-Borkowski, Rafal E.
Abstract: Abstract : Multilayers that comprise thin films of heavy metals and ferromagnets have been shown to host Néel-type magnetic skyrmions at room temperature. Fresnel defocus imaging in Lorentz transmission electron microscopy is a widely used technique for recording magnetic information about skyrmions. However, the visibility of Néel-type skyrmions in Fresnel defocus images is typically low, both because only a small component of their magnetic field contributes to the signal and because of the presence of diffraction contrast from the polycrystalline multilayer structure. Here, we take advantage of the out-of-plane hysteresis in such samples to record background-subtracted Fresnel defocus images. We demonstrate an improvement in magnetic signal-to-noise ratio and spatial resolution by a factor of 3 for a (Pt/Co/NiFe)×5 multilayer. We also use simulated Fresnel defocus images of Néel-type magnetic skyrmions to understand the influence of defocus on apparent skyrmion size.